STATISTICAL STUDY OF ECONOMIC CRIMES - D. Brailko (Вестник университета)
The article discusses the statistical reports of the Ministry of internal Affairs (MIA) of Russia on economic crimes. Describes new types of economic crimes that are not recorded in official statistics from the Ministry. Calculated property damage throughout the crime, as well as property damage only on economic crimes. Suggests methods to improve monitoring of economic crime.